VD_FINDINFO Pron / 2013 / 4 vom 11. Januar 2013 - VD Tribunal cantonal (2013)
TRANSACTION JUDICIAIRE, PROTECTION DE L'UNION CONJUGALE | 105 al. 1 CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH), 65 al. 2 TFJC (2010), 65 al. 3 TFJC (2010), 67 al. 2 TFJC (2010)